P26 Understanding the use of data for improvement. (20th March 2019) - Wagstaff, Duncan; Vindrola, Cecilia; Fulop, Naomi; Moonesinghe, Ramani
Abstract : Background: Using data for improvement is a national policy priority. 1 However, despite the considerable resources required to collect data for national clinical audits, their information is rarely used effectively to improve quality. 2 Barriers lie with the collection, analysis and feedback of these data, as well as with the capability, capacity and motivation of local teams to use them for improvement. 3 The perioperative setting encompasses the period before, during and after surgery and represents an increasingly recognised healthcare sector. 4 A scoping review we have conducted has confirmed that national clinical audit data is used inconsistently for local improvement of perioperative services. 5 The new national Perioperative Quality Improvement Programme (PQIP) aims to facilitate this use of data to improve perioperative services in the NHS. 6 Aim: This study seeks to explore whether, how, and in which contexts, perioperative data are currently used for quality improvement, and how this is affected by PQIP. Methods: A mixed-methods approach has been adopted comprising a national survey and qualitative fieldwork. The survey is gathering multidisciplinary staff experiences of using perioperative data and their perceptions of contextual factors. Findings from the survey will be triangulated with qualitative fieldwork in two case study hospitals, before and after they engage with PQIP. Furthermore, local understanding of PQIP's programme theory in these case study hospitals will be compared with that of the central PQIP project team to help understand any implementation gaps. Results: Data collection and analysis remains ongoing but will be available by March 2019. Conclusions: Using data for improvement in the NHS has often been an aspiration rather than an achievement due to difficulties posed by defining, measuring and improving quality. This study seeks to understand whether a theoretically derived program can overcome these barriers in the perioperative setting. References: National Improvement and Leadership Development Board. Developing People – Improving Care, 2016. Allwood D. Engaging Clinicians in Quality Improvement through National Clinical Audit. Rep to Health Qual Improv Partnersh . 2014;2014(October). The Royal College of Physicians and the Healthcare Quality Improvement Partnership. Unlocking the Potential Supporting Doctors to Use National Clinical Audit to Drive Improvement ; 2018. The Royal College of Anaesthetists. Perioperative Medicine the Pathway to Better Surgical Care ; 2015. University of York, Centre for Reviews and Dissemination. PROSPERO. https://www.crd.york.ac.uk/prospero/. CRD42018092993. www.pqip.org.uk.